Brief text analysis treatise of Abu Nasr al-Farabi "Kitab al-Adab al-Mulukiya wa al-Akhlaq al-Ikhtiyariyah" - Y.M. Paltore (Әл-Фараби Атындағы Қазақ Ұлттық Университеті хабаршы шығыстану сериясы, 2021)
A certain part of the treatises of Abu Nasr al-Farabi, who lived in the Middle Ages, has been translated into the Kazakh language. However, there are also treatises which have not entered into the scientific circulation yet. One of such treatises is the treatise "Kitab al-Adab al-Mulukiya wa al-Akhlaq al-Ikhtiyariyah" (كتاب الآداب الملوكية والأخلاق الإختيارية) (abbreviated as Kitab al-Akhlaq). This article provides information on the handwritten and printed versions of this treatise and its translations. Along with the translation into the Kazakh language of the initial part of the treatise, a short textual analysis of the original text is carried out. The article emphasizes that each new sentence of the treatise differs in that it begins with the verb "Qala" – (قال) "said", that is, "said Plato," and this word alone may indicate that al-Farabi is transmitting words of Plato. When Al-Farabi writes down his thoughts and philosophical explanations in the treatises that have come down to us, in fact he does not write that this is his (al-Farabi's) word. According to the tradition of that time, information about the author is written only on the first or last page of the work. Sometimes such a record containing important information about the author may not be in the manuscript. The discussed treatise also falls into this category. Only some versions of the manuscript indicate that this treatise was composed by al-Farabi. However, the study revealed that a certain part of the treatise we are discussing coincides with the text of one chapter under the heading "Al-Faaz al-Aflatun" in the book of al-Amir Usama ibn-Munqidh (الأمير أسامة بن منقذ) "Lubab al-Adab – لُبَابُ الآدبُ". The search also revealed that some of the sentences in the treatise were found in the book of the Arab philosopher al-Mubashshir ibn Fatik (المبشر بن فاتك) "Mukhtār al-Hikam wa maḥāsin al-kalim –مختار الحكم ومحاسن الكلم" On the first page of the manuscript of the Kitabul Akhlaq treatise, preserved in Egypt, it is said that the treatise belonged to Abu Nasr al-Farabi. Based on such written sources, we will consider this treatise as the legacy of al-Farabi.